2022
DOI: 10.5001/omj.2021.124
|View full text |Cite
|
Sign up to set email alerts
|

Frequency and Risk Factors of Diabetic Ketoacidosis in a Specialized Children’s Hospital, Riyadh: A Cross-sectional Study

Abstract: Objectives: Diabetic-ketoacidosis (DKA) is a life-threatening complication and a leading cause of hospitalization in Type-1-diabetes (T1DM) patients. We aimed to assess the risk factors of admissions of children with DKA in a specialized children hospital in order to reduce morbidity and to inform appropriate prevention and intervention strategies. Methods: A retrospective review of all DKA admissions at King Abdullah Specialized Children’s Hospital, Riyadh (March 2015–December 2017). Data were gathered from n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 20 publications
1
6
0
Order By: Relevance
“…The causes leading to prolonged admission after DKA resolution were similar between groups. Similarly, previous studies have reported prolonged admission after DKA resolution . Future interventions are needed to reduce prolonged hospitalization after DKA resolution.…”
Section: Discussionmentioning
confidence: 61%
See 3 more Smart Citations
“…The causes leading to prolonged admission after DKA resolution were similar between groups. Similarly, previous studies have reported prolonged admission after DKA resolution . Future interventions are needed to reduce prolonged hospitalization after DKA resolution.…”
Section: Discussionmentioning
confidence: 61%
“…Third, our study reflects the perspective of a single health care system with a small number of patients, although the DKA treatment costs and LOS at our center were similar to those of most public health care institutions in Saudi Arabia. The median LOS for mild DKA in Saudi Arabia is 2 to 4 days, whereas in the US health care system it is 3.22 days . Moreover, the costs of different health care resources used in the management of DKA are not significantly different from those of other health care systems with universal health care, such as the UK public health care system .…”
Section: Discussionmentioning
confidence: 97%
See 2 more Smart Citations
“…Diabetic ketoacidosis (DKA) is an acute complication of type 1 DM that may lead to severe morbidity and a life-threatening state of the disease, which might happen the first clinical presentation of newly diagnosed Type 1 diabetic children or might happen for the known cases of Type diabetic children through there life as a consequence of different etiologies [ 3 , 4 ].The incidence of DKA in newly diagnosed Type diabetic children varies dramatically among countries from 13 to 80 % inversely correlated to the prevalence of Type 1 DM in that country, and it is less common in adolescents compared to young children [ 5 ]. In Saudi Arabia the incidence of DKA in newly diabetic children [ 6 , 7 ].…”
Section: Introductionmentioning
confidence: 99%